The influence of illumination and cast shadows on prey detectability by predators - Cauchi, Lou; Reynolds, Keagan; Merilaita, Sami; Kelley, Jennifer (The Royal Society, 2026)
Many species use camouflage to dissimulate their true form and avoid detection or recognition. In natural habitats, the three-dimensional structure of an organism’s body can present challenges for camouflage, as overhead illumination creates luminance gradients (‘self-shadows’) across the body surface and cast shadows (when light is blocked by the object itself) on the surface behind the object. While self-shadows are known to increase prey detectability to predators, it is unclear whether this is also the case for cast shadows. We used computer-generated prey and live fish as predators (western rainbowfish; Melanotaenia australis) to investigate whether the illumination conditions and the presence of cast shadows increase the detectability of prey. In the first experiment, the background contained directional illumination cues, while in the second experiment, targets were presented on a homogeneous grey background. In both experiments, we found that neither the illumination conditions nor the presence of a cast shadow (nor their interaction) increased the probability of detection by predators, despite differences in luminance variation among the different prey stimuli. Our findings suggest that cast shadows do not provide additional contrast to that produced by self-shadows and that cast shadows do not provide depth cues that increase prey detectability by predators.